El color en el lenguaje cartográfico - Pellicer Corellano, Francisco (Geographicalia, 2017)
This study how the visual variable (colour) modifies and increases the power of the signification in the rest of the elements and visual factor, in the cartographical language, and it tries to elaborate a work methodology for users and map makers.
Keywords: Cartography; graphycal language; colour